Walkability and Urban Design in a Post-Earthquake City - Di Ludovico, Donato; Rizzi, Paola (TeMA - Journal of Land Use, Mobility and Environment, 2019)
The research described in this article concerns the issue of accessibility with a focus on the walkability in a city that is under reconstruction, such as the city of L'Aquila struck by a destructive earthquake in 2009. The reconstruction is determining a new urban layout in which there is a chaotic overlap of flows of the movements of vehicles and people, quite exceptional with respect to the configuration of an ordinary city. For example, the flows of heavy vehicles and work machines, linked to building reconstruction, and which also generate strong noise pollution and therefore a new soundscape, increase considerably. It is a city in which the return to the residences mixes with large building sites, in which urban transformations are very fast and must be governed through appropriate urban design instruments. The main aim of this research is to define a strategy to realize a method able to calculate at the same time an overlapping indexes in order to classify streets according to how friendly they are for the pedestrian and bike. This theme is approached to a methodological level and is related to the interacting theme of urban design and new centralities. The tool used for this integration is the Strategic Urban Project, which the research experience has found to be more effective and with greater performance than the more traditional Land Use Planning. The design approach and methodology is to integrate urban design techniques with spatial planning techniques, in order to obtain a higher performance of pedestrian networks.